1976
DOI: 10.1042/bj1600433
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium ions on testosterone production in Leydig cells from rat testis

Abstract: Leydig-cell suspensions, prepared from rat testes, were incubated with different amounts of Ca2+ with and without added luteinizing hormone. The basal testosterone production in the absence of luteinizing hormone was unaffected by the Ca2+ concentration in the incubation medium. The luteinizing hormone-stimulated testosterone production, however, was progressively decreased in the absence of Ca2+ to one-third of that with 2.50 mM-Ca2+. This decrease in luteinizing hormone-stimulated testosterone production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…PKC signaling is activated by arachidonic acid and the latter induces steroidogenic acute regulatory protein, leading to increased steroidogenesis (Janzen et al, 1976;Gudermann et al, 1992b). Calcium fluxes, triggered by LH binding, have also been shown to activate Leydig cell steroidogenesis (Janzen et al, 1976;Sullivan and Cooke, 1985;Gudermann et al, 1992b;Wang et al, 2000). In the present study, we observed that cal-cium-dependent signal transduction was required for stimulation of 11␤HSD reductive activity.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…PKC signaling is activated by arachidonic acid and the latter induces steroidogenic acute regulatory protein, leading to increased steroidogenesis (Janzen et al, 1976;Gudermann et al, 1992b). Calcium fluxes, triggered by LH binding, have also been shown to activate Leydig cell steroidogenesis (Janzen et al, 1976;Sullivan and Cooke, 1985;Gudermann et al, 1992b;Wang et al, 2000). In the present study, we observed that cal-cium-dependent signal transduction was required for stimulation of 11␤HSD reductive activity.…”
Section: Discussionsupporting
confidence: 57%
“…An indirect mechanism is seen, for example, in the case of testosterone itself, which has been shown to decrease 11␤HSD oxidative activity and increase reductive activity (Gao et al, 1997). Both PKC and calcium signaling have been shown to regulate testosterone production (Janzen et al, 1976;Nikula et al, 1987;Gudermann et al, 1992b). Both PKC and calcium/ calmodulin modulators could affect 11␤HSD via the action of testosterone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations